Communication of Dayak Ngaju’s Language in the Form of Local Families in Central Borneo, Indonesia - Liadi, Fimeir; ., Jasiah; Qudsiyah, Ummi; ., Mila; Irma Yanti, Nur (KnE Social Sciences, 2024)
This research will focus on the use of Dayak Ngaju communication related to the form of family greetings that can be seen from the completeness of its elements. Dayak Ngaju communication forms of family greetings are divided into three parts namely: complete greeting forms, incomplete greeting forms, and a combination of complete greeting forms and incomplete greeting forms. Based on the meaning and meaning of language communication, the form of family greetings includes the form of self-names, kinship terms, national titles, adjective transpositions, and beatings. The most influential factors of communication in the form of family greetings are: first, the seniority factor in terms of age, seniority is commonly known globally. The senior will hold the most influential string of honor. However, seniority in this tribe is related to the age of the oldest from the older people. So the oldest age position will hold the highest rope and receive the highest familial honor. As a reflection it is appropriate to be a leader in the family ties within the internal environment of their family, second is the level of rank in the family such as birth order. Based on this birth order, generally, families in this tribe will give honorary titles based on birth order. If the first sibling or first brother is not present then the authority to manage the family will be delegated to the sibling born in the second order. Keywords: communication, Dayak Ngaju, greeting form, polite language